Caracterização do erro de diagnóstico na hanseníase : fatores associados e impacto epidemiológico - Neves, Karine Vila Real Nunes (2021)
Introduction: Cases identified as misdiagnoses in leprosy should have treatment stopped immediately. Leprosy manifests itself through a variation of signs and symptoms that can make clinical diagnosis difficult. Objective: To analyze the magnitude of the error of diagnosis by leprosy in Brazil from 2003 to 2017, with emphasis on the clinical characteristics of patients with misdiagnosis in the State of Mato Grosso. Methods: A study developed in two stages 1. spatial and temporal analysis on the records of leprosy cases diagnosed in Brazil between 2003 and 2017 and that had their MDT treatment terminated due to "misdiagnosis"; 2. analysis of the reports of individuals who were diagnosed as new leprosy cases in the period from 2016 to 2019, and after starting treatment with multidrug therapy (MDT) were discharged due to misdiagnosis, according to the SINAN records of the state of Mato Grosso. Results: The detection rates of new leprosy cases in Brazil decreased in 15 years from 29.0 to 12.8 per 100,000 inhabitants, while the proportion of leprosy exits due to misdiagnosis remained stable and showed no spatial correlation with the detection rates or change in the spatial distribution pattern. Female gender, age group under 15 years, undetermined clinical form, absence of skin lesions at diagnosis, presence of affected nerves at diagnosis, and mode of detection by collective examinations and by contact examinations were associated with high diagnostic error. The 162 interviewees reported fibromyalgia, back problems, and absence of any disease as conclusive diagnosis most frequently. Among those without any disease, most were contacts of a leprosy case. The individuals with misdiagnosis sought other health services with some dissatisfaction with the diagnosis or treatment, including presenting adverse effects to medication. Conclusion: The proportion of misdiagnoses in leprosy is not related to the level of endemicity in Brazil, but rather to patient characteristics and clinical manifestations, being more likely for those whose clinical manifestations are less evident. The conclusive diagnosis, reported by the participants, resulted in aggravations not always considered as a differential diagnosis - such as fibromyalgia and back problems - in addition to the absence of disease. It is noteworthy that those who reported having no disease were mostly contacts of someone with leprosy, which points to flaws in the understanding of the surveillance protocol regarding contacts. The study points to failures in the diagnosis, in the treatment follow-up as to adverse effects. It is suggested continued training of health professionals, complementary tests in more complex and doubtful diagnoses to reduce false diagnoses in leprosy.